Species Pervasiveness Within the Group of Coagulase-Negative Staphylococci Associated With Meat Fermentation Is Modulated by pH - Stavropoulou, Despoina Angeliki; De Maere, Hannelore; Berardo, Alberto; Janssens, Bente; Filippou, Panagiota; De Vuyst, Luc; De Smet, Stefaan; Leroy, Frédéric (Frontiers in Microbiology, 2018)
During spontaneous meat fermentations, Staphylococcus equorum, Staphylococcus saprophyticus, and Staphylococcus xylosus are generally the most prevailing species within the communities of coagulase-negative staphylococci (CNS). There is an interest to introduce CNS isolates from artisan-style spontaneous meat fermentations as starter cultures in more industrialized processes, as to confer additional quality benefits. However, staphylococcal competitiveness within the meat matrix is affected by the processing conditions, which vary considerably among product types. A major factor of variability relates to the intensity of acidification, driven by the concentration of added carbohydrates. The effect of pH on CNS prevalence was studied in both a mince-based meat fermentation model and in fermented sausages produced on pilot scale. Roughly, from all experiments combined, it appeared that a pH of 5.3 corresponded with a breakpoint for CNS selection. Above this value, a general prevalence by S. xylosus was found, even overruling the addition of starter cultures consisting of S. equorum and S. saprophyticus strains. At pH values below 5.3, S. xylosus was also accompanied by S. equorum (following a mild pH drop) and S. saprophyticus (following a stronger pH drop). Still, addition of starter cultures affected the volatile profile compared to the control batch, even if those starter cultures were not able to dominate during the ripening process. This study nonetheless provides a warning for an overly confident use of specific CNS species as starter cultures, especially when in a given processing context the prevailing conditions do not allow superior growth compared to the CNS from the background microbiota.